2015
DOI: 10.3892/ol.2015.4044
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of cancer cell migration by lung cancer cell-derived exosomes through TGF-β and IL-10

Abstract: Abstract. Tumorigenesis has been considered to be as a result of abnormal cell-cell communication. It has been proposed that exosomes act as communicators between tumors and their microenvironment and have been demonstrated to be involved in tumorigenesis and subsequent metastasis. However, the mechanisms underlying the role of exosomes in these processes remains elusive. The present study sought to determine the underlying mechanisms. Using two lung cancer cell lines, it was demonstrated that exosomes derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 27 publications
0
58
0
Order By: Relevance
“…For example, exosomes released from gastric cancer cells can trigger the differentiation of umbilical cord-derived mesenchymal stem cells into carcinoma-associated fibroblasts via the transfer of TGF-β 23 . Lung cancer cell-derived exosomes can regulate the tumor cells migration by transferring TGF-β 24 . In cancer, the exosomal delivery of TGF-β is capable of driving fibroblast-to-myofibroblast differentiation 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, exosomes released from gastric cancer cells can trigger the differentiation of umbilical cord-derived mesenchymal stem cells into carcinoma-associated fibroblasts via the transfer of TGF-β 23 . Lung cancer cell-derived exosomes can regulate the tumor cells migration by transferring TGF-β 24 . In cancer, the exosomal delivery of TGF-β is capable of driving fibroblast-to-myofibroblast differentiation 25 .…”
Section: Introductionmentioning
confidence: 99%
“…As potent immunosuppressive cytokines, IL-10 and TGF-b1 have been demonstrated to be the mediators of TEX promotion of tumor development. [41][42][43] Building on our hypothesis, abolishment of their expression in parental cells can produce TEXs without IL-10 and/or TGF-b1, which likely convert tumor-promoting TEXs to tumor-inhibitory TEXs. In addition, in this way, TEXs with original antitumor effects might greatly increase their antitumor effect.…”
Section: Discussionmentioning
confidence: 86%
“…Exosomes can transmit mutant EGFR into tumor-associated vascular endothelial cells and activate MAPK signaling, which will promote endothelial cell proliferation [11]. Studies by Wang et al found that TGF-β and IL-10 from cancer-derived exosomes are also involved in the regulation of cell proliferation and metastasis and their high expression can promote lung cancer cell growth and metastasis [12]. Rahman et al showed that exosomes that are from high invasive potential lung cancer cells can induce the expression of vimentin in recipient cells, which will drive the recipient cells to undergo epithelial transformation, resulting in upregulation of invasion and migration ability [13].…”
Section: Exosomes Mediate Lung Cancer Invasion -Metastasismentioning
confidence: 99%